Self‐adaptation on parallel stream processing: A systematic review. (7th December 2021) - Vogel, Adriano; Griebler, Dalvan; Danelutto, Marco; Fernandes, Luiz Gustavo
Summary: A recurrent challenge in real‐world applications is autonomous management of the executions at run‐time. In this vein, stream processing is a class of applications that compute data flowing in the form of streams (e.g., video feeds, images, and data analytics), where parallel computing can help accelerate the executions. On the one hand, stream processing applications are becoming more complex, dynamic, and long‐running. On the other hand, it is unfeasible for humans to monitor and manually change the executions continuously. Hence, self‐adaptation can reduce costs and human efforts by providing a higher‐level abstraction with an autonomic/seamless management of executions. In this work, we aim at providing a literature review regarding self‐adaptation applied to the parallel stream processing domain. We present a comprehensive revision using a systematic literature review method. Moreover, we propose a taxonomy to categorize and classify the existing self‐adaptive approaches. Finally, applying the taxonomy made it possible to characterize the state‐of‐the‐art, identify trends, and discuss open research challenges and future opportunities.